Information-entropy method for detecting gravitational wave signals - Zhanabaev, Z.Zh.; Ussipov, N.M. (Karagandy University of the name of acad. E.A. Buketov, 2023)
The detection of gravitational waves came from a pair of merging black holes marked the beginning of the era of GW astronomy. Traditionally, to extract gravitational wave signals from experimental data, the scientific collaborations use the standard matched filtering technique. The matched filtering technique relies on the existing waveform templates, that makes it difficult to find gravitational wave signals that go beyond theoretical expectations. Moreover, the computational cost of matched filter is very high, as it depends on the number of templates used. In this article, we propose a new information-entropy method for gravitational waves detection that does not require a theoretical bank of signal templates. To demonstrate the reliability of our method we conducted an analysis using simulated and real data. Through this study, we revealed that our measure of conditional information detects the gravitational wave signals and can be used along with the matched filtering method.
Keywords: gravitational waves; information-entropy; detection; nonlinear process